Dispersing agent as well as preparation method and application thereof

By preparing low-molecular weight polymers containing methyl and carboxyl functional groups as dispersants, and combining airflow crushing and sintering technology, the problem of improving compaction density and electrochemical performance of lithium iron phosphate positive electrode materials is solved, and high compaction density and excellent electrochemical performance are achieved.

CN119899308APending Publication Date: 2025-04-29HUBEI WANRUN NEW ENERGY TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510112357.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, it is difficult to greatly improve the compaction density and electrochemical properties of lithium iron phosphate positive electrode materials, mainly due to the poor dispersion of small particle agglomerates and the difficulty in precise control of dopant doping.

Method used

By preparing a low-molecular-weight polymer containing functional groups such as methyl and carboxyl groups as a dispersant, the adsorption and dispersion of the dispersant are improved by using polymerization reaction, and combined with airflow pulverization and sintering technology during the preparation of lithium iron phosphate, the particle grading and dopant distribution are optimized.

Benefits of technology

The compaction density and electrochemical performance of lithium iron phosphate positive electrode material are improved, and a higher 1C discharge specific capacity and charge and discharge efficiency are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899308A_ABST
    Figure CN119899308A_ABST
Patent Text Reader

Abstract

The invention provides a dispersing agent and a preparation method and application thereof, and belongs to the technical field of lithium batteries, the preparation method of the dispersing agent comprises the following steps: taking a first monomer, a second monomer, a chain transfer agent and an initiator as raw materials, and carrying out polymerization reaction at 45-75 DEG C to obtain the dispersing agent, wherein the first monomer comprises one or more of diethyl methyl vinyl silane, methyl vinyl bis (N-methyl acetamido) silane and 3-(dimethylamino) methyl acrylate, and the second monomer comprises one or more of methacrylic acid, 3-ethoxyacrylic acid and 2-hydroxy-2-methyl-3-butenoic acid. The dispersing agent prepared in the invention has strong adsorbability and strong dispersibility, and can improve the dispersibility of small particles in the preparation process of the lithium iron phosphate positive electrode material, so that the prepared lithium iron phosphate particles have no obvious adhesion, the particle size distribution interval is increased, and the compaction density and electrochemical performance of the lithium iron phosphate positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a dispersant and a preparation method and application thereof. Background Art

[0002] Modified lithium iron phosphate is often used in batteries in the field of new energy vehicles, and the main methods for modifying lithium iron phosphate are carbon coating and doping. Carbon coating plays a major role in the dispersion and particle size regulation of lithium iron phosphate particles. Currently, the commonly used carbon sources for the preparation of lithium iron phosphate are mostly non-ionic polymers such as glucose, sucrose, and PEG. These organic carbon sources are mainly carbonized and deposited through a sintering carbonization process, and carbonized to inhibit particle adhesion and growth. However, the above-mentioned carbon sources have poor adsorption and dispersibility for iron phosphate. Even if PEG has the function of a surfactant, it can only regulate the slurry state through surface activity due to its poor adsorption. Small particle agglomerates are prone to aggregation in the slurry. Therefore, when using common carbon sources to prepare modified lithium iron phosphate, there is poor dispersion of small particle agglomerates during the sintering process. There are many agglomerates in the particles below D50 in the sintered crushed material, which makes the product porosity high and the particle size distribution range narrow, resulting in the problem that the compaction density of the finished modified lithium iron phosphate is difficult to be greatly improved, thereby affecting the electrochemical properties of the lithium iron phosphate positive electrode material; on the other hand, dopants can improve the electrochemical properties of modified lithium iron phosphate, but too high a doping amount will reduce the compaction density of the modified lithium iron phosphate, thereby having a negative impact on the electrochemical performance. Therefore, when using dopants to prepare modified lithium iron phosphate, there is also a problem that the compaction density and electrochemical performance need to be further improved.

[0003] In the related art, the common method to improve the compaction density of modified lithium iron phosphate is particle grading, but the current pulverization conditions have a poor pulverization effect on particles below D50 of sintered lithium iron phosphate positive electrode materials, resulting in a small proportion of small particles, a narrow actual particle size distribution of the finished product, many small particle agglomerates and poor dispersibility, and it is difficult to increase the compaction density, thereby affecting the electrochemical performance of the material. Therefore, it is necessary to provide a method that can simultaneously improve the compaction density and electrochemical performance of lithium iron phosphate. Summary of the invention

[0004] In view of the technical problems existing in the background technology, the present application provides a dispersant and a preparation method and application thereof, aiming to solve the problem of how to improve the compaction density and electrochemical performance of lithium iron phosphate positive electrode materials.

[0005] In the first aspect, an embodiment of the present application provides a method for preparing a dispersant, comprising the following steps: using a first monomer, a second monomer, a chain transfer agent, and an initiator as raw materials, and performing a polymerization reaction at 45-75° C. to obtain a dispersant; wherein the first monomer includes one or more of diethylmethylvinylsilane, methylvinylbis(N-methylacetylamino)silane, and 3-(dimethylamino)methylacrylate, and the second monomer includes one or more of methacrylic acid, 3-ethoxyacrylic acid, and 2-hydroxy-2-methyl-3-butenoic acid.

[0006] In the technical solution of the embodiment of the present application, a polymerization reaction is carried out on the specified raw materials to obtain a low molecular weight polymer containing functional groups such as methyl and carboxyl groups, which has strong adsorption and dispersibility, and is beneficial to improving the dispersibility of small particles in the preparation process of lithium iron phosphate positive electrode materials, so that the adhesion between small particles can be improved, and the particle size distribution range can be increased, thereby improving the compaction density of the prepared lithium iron phosphate positive electrode material, and further improving the electrochemical performance of the lithium iron phosphate positive electrode material prepared using the dispersant.

[0007] In some embodiments, the chain transfer agent includes at least one of thioglycolic acid and mercaptopropionic acid; the initiator includes at least one of azobisisobutyronitrile and ammonium persulfate.

[0008] In this embodiment, the chain transfer agent and the initiator are used to achieve polymerization of the first monomer and the second monomer to obtain a low molecular weight polymer having functional groups such as methyl and carboxyl groups and having strong adsorption and dispersibility.

[0009] In some embodiments, the molar ratio of the first monomer, the second monomer, the chain transfer agent, and the initiator is 1:(5-8):(0.015-0.02):(0.05-0.10).

[0010] In this embodiment, adjusting the ratio of the dispersant raw materials is beneficial to balancing the adsorption and dispersion properties of the prepared dispersant. If the amount of the first monomer and the second monomer is reduced, the active functional groups in the dispersant will be reduced, and its dispersibility and adsorption will be reduced; if the amount of the first monomer and the second monomer is too much, it will lead to a waste of raw materials; if the amount of the chain transfer agent and the initiator is reduced, it will lead to a decrease in the yield of the dispersant; and if the amount of the chain transfer agent and the initiator is too much, it will cause a waste of raw materials.

[0011] In a second aspect, an embodiment of the present application provides a dispersant, which is prepared by the preparation method of the dispersant in the first aspect.

[0012] In the technical solution of the embodiment of the present application, when the dispersant is used for the preparation of lithium iron phosphate, the dispersant can improve the dispersibility and adsorption of carbon sources and small particle agglomerates. At the same time, it can also reduce the viscosity of the slurry and reduce the risk of blockage, thereby improving the production efficiency of lithium iron phosphate positive electrode materials.

[0013] In a third aspect, an embodiment of the present application provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps: adding anhydrous iron phosphate, a lithium source, a carbon source, and a dispersant to a solvent and mixing them to obtain a slurry; dispersing the slurry, and then adding a dopant to the slurry to obtain a precursor slurry; spray drying, air flow crushing, and sintering the precursor slurry in sequence to obtain a lithium iron phosphate positive electrode material.

[0014] In the technical solution of the embodiment of the present application, by adding a dispersant to the slurry, adding the undispersed dopant to the dispersed slurry and combining the methods of air flow crushing and then sintering, the lithium iron phosphate has the following advantages: (1) the carbon source has good encapsulation and dispersion, the degree of graphitization is high, and the conductivity of the material is good; (2) the particles have good dispersion, the particle grading is reasonable, and the compaction density is high; (3) the dopant content is high; (4) the magnetic material content is low; the above advantages can realize the improvement of the charge and discharge capacity and charge and discharge efficiency of the lithium iron phosphate positive electrode material.

[0015] In some embodiments, the solid content of the slurry is 45%-50%, and the density of the slurry is ≥1.2g / cm 3 ; The D50 of the slurry after dispersion treatment is 0.36-0.45μm, and the Dmax of the sand-milled mixture is ≤1.15μm; the process parameters of air flow milling include: the pressure of air flow milling is 0.48-0.52MPa, the frequency of the classifying wheel is 20-60Hz, and the feeding frequency is 6-18Hz; the D50 of the particles after air flow milling is 0.6-1.2μm, and Dmax is ≤15μm.

[0016] In this embodiment, the slurry is dispersed to increase the proportion of small particles, and forms evenly dispersed small particles under the action of the dispersant, thereby adjusting the grading of the finished particles, and further improving the compaction density of the prepared lithium iron phosphate positive electrode material; further, the airflow milling method is beneficial to reduce the content of magnetic substances and improve the electrochemical properties of the material; at the same time, the dispersion treatment step overcomes the defect that the airflow milling has a poor crushing effect on small particle agglomerates, and the D50 of the solid particles contained in the slurry after the dispersion treatment is less than the D50 of the particles after the airflow milling. This process condition can reduce the negative impact of the dopant on the compaction density of the prepared lithium iron phosphate positive electrode material.

[0017] In some embodiments, the mass ratio of anhydrous ferric phosphate to the lithium source, the carbon source and the dispersant is 100:(22-26):(8-12):(0.4-1.2); and / or, the mass ratio of the dispersant to the dopant is (0.41-0.85):1; and / or, the carbon source includes at least one of glucose and sucrose; and / or, the dopant includes at least one of tin dioxide, titanium dioxide, and cerium oxide; and / or, the lithium source includes at least one of lithium carbonate, lithium chloride, lithium nitrate, and lithium hydroxide.

[0018] In this embodiment, the use of dispersant within a limited range is beneficial to improving the compaction density of lithium iron phosphate. If the amount of dispersant is too little, the compaction density will be reduced. If the amount of dispersant is too much, it will cause waste of raw materials. The use of dopant must be within a limited range to help improve the capacity of lithium iron phosphate. If the amount of dopant is too much or too little, it will not be conducive to improving the capacity of lithium iron phosphate.

[0019] In some embodiments, the sintering temperature is 790° C.-800° C., and the sintering atmosphere is an inert atmosphere.

[0020] In this embodiment, by controlling the sintering temperature within the above range, the following effects are achieved: (1) it is conducive to reducing the proportion of large single crystal particles and stabilizing the compaction density; (2) it is conducive to improving the carbon coating effect and reducing the internal resistance of the powder; (3) it is conducive to improving the purity of the lithium iron phosphate positive electrode material; (4) it reduces the content of magnetic substances. Therefore, the compaction density and electrochemical performance of the lithium iron phosphate positive electrode material prepared at the above sintering temperature are improved.

[0021] In a fourth aspect, an embodiment of the present application provides a lithium iron phosphate positive electrode material, and the 1C discharge specific capacity of the lithium iron phosphate positive electrode material is 146-147 mAh / g; the compaction density of the lithium iron phosphate positive electrode material is 2.62-2.68 g / mL.

[0022] In the technical solution of the embodiment of the present application, the compaction density and discharge specific capacity of the prepared lithium iron phosphate positive electrode material are both high.

[0023] In a fifth aspect, an embodiment of the present application provides a secondary battery comprising a lithium iron phosphate positive electrode material.

[0024] In the technical solution of the embodiment of the present application, the secondary battery contains the above-mentioned lithium iron phosphate positive electrode material, and thus also has better electrochemical performance.

[0025] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Example 5; Figure 2 This is a particle size distribution detection diagram of the lithium iron phosphate positive electrode material prepared in Example 5; Figure 3 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Comparative Example 1; Figure 4 This is a particle size distribution detection diagram of the lithium iron phosphate positive electrode material prepared in Comparative Example 1; Figure 5 The Raman spectra of the lithium iron phosphate positive electrode materials prepared in Example 5 and Comparative Example 1; Figure 6 3, 5 and 1. The particle size distribution curve of the crushed lithium iron phosphate positive electrode material of Example 3, Example 5 and Comparative Example 1. DETAILED DESCRIPTION

[0028] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0030] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0031] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0032] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0033] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0034] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.

[0035] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0036] In the prior art, the modification methods of lithium iron phosphate are mainly carbon coating and doping. Carbon coating plays a great role in the dispersion and particle size regulation of lithium iron phosphate particles. Among them, the commonly used carbon sources in the preparation of lithium iron phosphate are mostly non-ionic polymers such as glucose, sucrose, and PEG. These organic carbon sources are mainly carbonized and deposited through sintering and carbonization processes, and carbonized to inhibit the adhesion and growth of particles. However, their adsorption and dispersibility for iron phosphate are poor. Even though PEG has the function of a surfactant, due to its poor adsorption, it can only regulate the slurry state through surface activity, and small particle agglomerates are prone to aggregation in the slurry. Therefore, when using common carbon sources to prepare modified lithium iron phosphate, small particles are prone to agglomerate to form agglomerates during the sintering process, resulting in poor dispersion of the particles, which in turn makes the product have high porosity and a narrow particle size distribution range, resulting in difficulty in significantly improving the compaction density of the finished modified lithium iron phosphate, thereby affecting the electrochemical properties of the lithium iron phosphate positive electrode material; on the other hand, dopants can improve the electrochemical properties of modified lithium iron phosphate, but excessive doping levels will reduce the compaction density of the modified lithium iron phosphate, thereby having a negative impact on the electrochemical properties. Therefore, precise control of the amount of dopant used will affect the physical and electrochemical properties of the modified lithium iron phosphate. The use of dopants to prepare modified lithium iron phosphate also has the problem that the compaction density and electrochemical properties need to be further improved.

[0037] In order to solve the technical problem of how to improve the compaction density and electrochemical performance of lithium iron phosphate positive electrode materials, the present application provides a dispersant and a preparation method and application thereof, and the obtained lithium iron phosphate positive electrode material has a high compaction density and good electrochemical performance.

[0038] In the first aspect, an embodiment of the present application provides a method for preparing a dispersant, comprising the following steps: using a first monomer, a second monomer, a chain transfer agent, and an initiator as raw materials, and performing a polymerization reaction at 45-75° C. to obtain a dispersant; wherein the first monomer includes one or more of diethylmethylvinylsilane, methylvinylbis(N-methylacetylamino)silane, and 3-(dimethylamino)methylacrylate, and the second monomer includes one or more of methacrylic acid, 3-ethoxyacrylic acid, and 2-hydroxy-2-methyl-3-butenoic acid.

[0039] In the technical scheme of the embodiment of the present application, a polymerization reaction is carried out on the specified raw materials to obtain a low molecular weight polymer containing functional groups such as methyl and carboxyl groups. The low molecular weight polymer has strong adsorption and dispersibility, which is beneficial to improve the dispersibility of small particle agglomerates in the process of preparing modified lithium iron phosphate, reduce the degree of adhesion of small particles, and make the finished modified lithium iron phosphate particles easier to separate without obvious adhesion. The particle size is small and the particle size distribution range is enlarged, which can play the filling role of small particles, realize the improvement of particle grading and compaction density, thereby improving the electrochemical properties of lithium iron phosphate positive electrode materials.

[0040] Among them, the mechanism by which the dispersant improves the dispersibility of small particle agglomerates is that: (1) the methyl content in the dispersant is high, which has a good steric hindrance to provide repulsion, and the carboxyl group of the dispersant forms a coating layer on the surface of the particles to separate the small particles, which together enhances the dispersibility of the dispersant; (2) the carboxyl group contained in the dispersant is hydrophilic, and because the particle size of the slurry after sand grinding is small and the specific surface area is large, the amount of adsorption of the dispersant on the sand grinding slurry increases, which together improves the adsorption performance of the dispersant. Therefore, the embodiment of the present application achieves the dispersion of small particles by improving the dispersibility and adsorption performance of the dispersant to avoid the formation of small particle agglomerates.

[0041] Further, in some embodiments, the chain transfer agent includes at least one of thioglycolic acid and mercaptopropionic acid; and / or, the initiator includes at least one of azobisisobutyronitrile and ammonium persulfate.

[0042] In the technical solution of the embodiment of the present application, the chain transfer agent and the initiator are used to realize the polymerization of the first monomer and the second monomer to obtain a low molecular weight polymer containing functional groups such as methyl and carboxyl groups and having strong adsorption and dispersibility.

[0043] Further, in some embodiments, the molar ratio of the first monomer, the second monomer, the chain transfer agent, and the initiator is 1:(5-8):(0.015-0.02):(0.05-0.10); for example, the molar ratio of the first monomer, the second monomer, the chain transfer agent, and the initiator is 1:5:0.02:0.1, 1:6:0.02:0.1, 1:7:0.02:0.1, 1:8:0.02:0.1 or any ratio between 1:(5-8):(0.015-0.02):(0.05-0.10).

[0044] In the technical scheme of the embodiment of the present application, adjusting the ratio of the dispersant raw materials is beneficial to balancing the adsorption and dispersion performance of the prepared dispersant. Among them, if the amount of the first monomer and the second monomer is reduced, it will lead to a reduction in the active functional groups in the dispersant, thereby reducing its dispersibility and adsorption; if the amount of the first monomer and the second monomer is too much, it will lead to a waste of raw materials; a reduction in the amount of chain transfer agent and initiator will lead to a decrease in the yield of the dispersant; an excessive amount of chain transfer agent and initiator will cause a waste of raw materials.

[0045] In some embodiments, the first monomer is a mixture of methylvinylbis(N-methylacetylamino)silane and 3-(dimethylamino)methyl acrylate, and the second monomer is a mixture of 3-ethoxyacrylic acid and 2-hydroxy-2-methyl-3-butenoic acid. Under the usage limit of the first monomer, the second monomer, the chain transfer agent, and the initiator in a molar ratio of 1:(5-8):(0.015-0.02):(0.05-0.10), the chemical formula of the obtained dispersant is as follows: ; Among them, a=3, 4, b=1, 2, c=3, 4, 5, d=2, 3, 4.

[0046] In a second aspect, an embodiment of the present application provides a dispersant obtained, which is prepared by the preparation method of the dispersant in the first aspect mentioned above.

[0047] In the technical solution of the embodiment of the present application, the dispersant improves the dispersibility and adsorption of the carbon source and small particles, and at the same time, can reduce the viscosity of the slurry, thereby reducing the risk of blockage and improving production efficiency.

[0048] In a third aspect, an embodiment of the present application provides a method for preparing lithium iron phosphate, comprising the following steps: adding anhydrous iron phosphate, a lithium source, a carbon source, and a dispersant to a solvent and mixing them to obtain a slurry; dispersing the slurry, and then adding a dopant to the slurry to obtain a precursor slurry; spray drying, air flow crushing, and sintering the precursor slurry in sequence to obtain lithium iron phosphate.

[0049] In the present application, by adding a dispersant to the slurry, adding the dopant to the dispersed slurry without dispersion treatment, and combining the methods of air flow crushing and then sintering, the lithium iron phosphate has the following advantages: (1) the carbon source has good encapsulation and dispersion, a high degree of graphitization, and good conductivity of the material; (2) the particles have good dispersion, reasonable particle grading, and high compaction density; (3) the dopant content is high; (4) the magnetic material content is low. The above advantages achieve the improvement of the electrochemical performance of lithium iron phosphate.

[0050] The mechanism of the above advantages is: by adding dispersant to the slurry, on the one hand, the dispersion and adsorption of small particle agglomerates are improved, ensuring that small particle agglomerates are evenly dispersed during sintering, the dispersion of large and small particles is good, the proportion of small particles is high, the finished product particle size and the primary particle distribution range are wide, so the particle grading is reasonable and the dispersion is good, thereby improving the compaction density and the electrochemical properties of the material are good; on the other hand, the dispersion and adsorption of the carbon source are improved, the carbon source is evenly distributed, and the encapsulation and dispersibility of the carbon source are good, resulting in a good carbonization effect and a high degree of graphitization, which improves the conductive properties of the material, reduces the internal resistance of the powder, and is beneficial to the improvement of the charge and discharge capacity.

[0051] As known to those skilled in the art, doping elements enter the lithium iron phosphate by melting and diffusion to form defects, thereby improving the diffusion performance of lithium ions. However, doping will inhibit the continued growth of particles, affect the grading, and thus reduce the electrochemical properties of lithium iron phosphate. In the present application, unsanded dopants are added after the slurry is sand-ground. The particle size of the dopant is larger than the particle size of the slurry after sand-ground, and the reaction will be slower during the sintering process. The doping elements are not in direct contact with the particles, reducing the negative impact of the doping elements after sand-ground on the growth of lithium iron phosphate particles. The normal growth of some primary particles is controlled to achieve particle grading. On the basis of ensuring the compaction density, the amount of dopant can be increased to increase the charge and discharge capacity, thereby overcoming the problem of difficulty in compacting and improving the finished product due to high doping amounts.

[0052] In the present application, the precursor is first pulverized by air flow and then sintered. The particles are heated more evenly and grow more fully. The large particle size is controllable, which is conducive to more complete sintering and can achieve sufficient reaction at a lower sintering temperature, thereby preparing high-density lithium iron phosphate with good capacity. The sintered lithium iron phosphate positive electrode material can be directly used as a finished product for higher testing efficiency.

[0053] Further, in some embodiments, the solid content of the slurry is 45%-50%, for example, 45%, 46%, 47%, 48%, 49%, 50% or any value between 45%-50%, and the density of the slurry is ≥1.2 g / cm 3 , for example 1.2 g / cm 3 , 1.5g / cm 3 , 2.0g / cm 3 , 2.5g / cm 3 ≥1.2g / cm 3 The D50 of the slurry after dispersion treatment is 0.36-0.45 μm, such as 0.36 μm, 0.4 μm, 0.45 μm or any value between 0.36-0.45 μm, and the Dmax of the slurry after dispersion treatment is ≤1.15 μm, such as 1.15 μm, 1 μm, 0.5 μm or any value ≤1.15 μm; the process parameters of air flow milling are as follows: the air flow milling pressure is 0.48-0.52 MPa, such as 0.48 MPa, 0.5 MPa, 0.52 MPa or 0.48-0 .52MPa, the classifying wheel frequency is 20-60Hz, for example, 20Hz, 40Hz, 60Hz or any value between 20-60Hz, the feeding frequency is 6-18Hz, for example, 6Hz, 10Hz, 18Hz or any value between 6-18Hz; the D50 of the particles after airflow crushing is 0.6-1.2μm, for example, 0.6μm, 1μm, 1.2μm or any value between 0.6-1.2μm, and Dmax≤15μm, for example, 15μm, 10μm or any value ≤15μm.

[0054] In the technical solution of the embodiment of the present application, the dispersed slurry is conducive to increasing the proportion of small particles, and under the action of the dispersant, a uniformly dispersed agglomerate of small particles is formed, thereby adjusting the gradation of the finished particles, and then improving the compaction density of the prepared lithium iron phosphate positive electrode material; the pulverization method of airflow pulverization is conducive to reducing the content of magnetic substances and improving the electrochemical properties of the material; at the same time, the dispersion treatment can overcome the defect that the airflow pulverization has a poor pulverization effect on small particle agglomerates, and the D50 of the solid particles contained in the slurry after the frosting treatment is less than the D50 of the particles after the airflow pulverization. This process condition limitation can reduce the negative impact of the dopant on the compaction density of the finished product. Preferably, the dispersion treatment is a frosting treatment.

[0055] As known to those skilled in the art, after the same sample is crushed, as the crushed particle size decreases, the secondary agglomerated particles will gradually decrease, the dispersibility of small particles will be significantly improved, and the compaction will gradually increase; however, compared with other crushing methods, the smaller the crushed particle size of airflow crushing, the lower the compaction density will be. The reason is that the fixed gap of the grading wheel of airflow crushing will cause small particles to escape, the crushing effect of small particles is not good, and the small particles are in a agglomerated state and cannot play a filling role; however, compared with other crushing methods, airflow crushing can ensure that the magnetic particles are low, which is beneficial to improving the electrochemical properties of the material. On the basis of retaining the crushing method of airflow crushing, the present application improves the dispersibility of small particles by adding a dispersant, ensures that the small particles are evenly dispersed to play a filling role and increase the compaction density, thereby improving the electrochemical performance.

[0056] Furthermore, in some embodiments, the mass ratio of anhydrous ferric phosphate to the lithium source, the carbon source and the dispersant is 100:(22-26):(8-12):(0.4-1.2); and / or, the mass ratio of the dispersant to the dopant is (0.41-0.85):1; and / or, the carbon source includes at least one of glucose and sucrose; and / or, the dopant includes at least one of tin dioxide, titanium dioxide, and cerium oxide; and / or, the lithium source includes at least one of lithium carbonate, lithium chloride, lithium nitrate, and lithium hydroxide.

[0057] In the technical solution of the embodiment of the present application, the use of dispersant within a limited range is beneficial to improving the compaction density of lithium iron phosphate. If the amount of dispersant is too little, the compaction density will be reduced. If the amount of dispersant is too much, it will cause waste of raw materials. The use of dopant must be within a limited range to be beneficial to improving the capacity of lithium iron phosphate. If the amount of dopant is too much or too little, it will not be conducive to improving the capacity of lithium iron phosphate.

[0058] Furthermore, in some embodiments, the sintering temperature is 790° C.-800° C., and the sintering atmosphere is an inert atmosphere.

[0059] In the technical solution of the embodiment of the present application, by controlling the sintering temperature within the above range, the following effects are achieved: (1) It is conducive to reducing the proportion of large single crystal particles and stabilizing the compaction density; (2) It is conducive to improving the carbon coating effect and reducing the internal resistance of the powder; (3) It is conducive to improving the purity of lithium iron phosphate; (4) It reduces the content of magnetic substances. Therefore, the compaction density and electrochemical performance of the lithium iron phosphate positive electrode material prepared at the above sintering temperature are improved.

[0060] Under the premise that the present application combines the means of adding a dispersant to the slurry, adding the dopant to the sand-milled mixture without sand-milling, and first air flow pulverizing and then sintering, the present application can achieve low-temperature sintering while improving the compaction density and electrochemical performance.

[0061] In a fourth aspect, an embodiment of the present application provides a lithium iron phosphate positive electrode material, and the 1C discharge specific capacity of the lithium iron phosphate positive electrode material is 146-147 mAh / g; the compaction density of the lithium iron phosphate positive electrode material is 2.62-2.68 g / mL.

[0062] In the technical solution of the embodiment of the present application, the lithium iron phosphate positive electrode material has a high compaction density and good charge and discharge performance.

[0063] In a fifth aspect, an embodiment of the present application provides a secondary battery comprising a lithium iron phosphate positive electrode material.

[0064] In the technical solution of the embodiment of the present application, the secondary battery contains the above-mentioned lithium iron phosphate positive electrode material, and thus has the advantages of reduced volume, prolonged standby time, and prolonged service life.

[0065] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0066] 1. Preparation method Example 1 A method for preparing a lithium iron phosphate positive electrode material comprises the following steps: 1 mol of methylvinylbis(N-methylacetylamino)silane was added with pure water to prepare a 2.5 mol / L solution, which was then added into a reaction kettle for stirring and heating. When the temperature reached 45°C, 0.5 mol / L A solution prepared with 0.08 mol of azobisisobutyronitrile and 10 mol / L B solution prepared with 4 mol of methacrylic acid, 2 mol of 2-hydroxy-2-methyl-3-butenoic acid and 0.017 mol of thioglycolic acid were simultaneously added dropwise. The B solution was added dropwise for 50 min, and the A solution was added dropwise for 60 min. During the reaction, the reaction temperature was controlled to be 60°C. After the A solution was added dropwise, the reaction was kept warm for 30 min, and the solution was cooled to room temperature to obtain an aqueous solution of a dispersant with a solid content of 40%. The iron phosphate with an iron-phosphorus ratio of 1:1.03, lithium carbonate accounting for 24.92% of the mass fraction of iron phosphate, monohydrate glucose accounting for 9.8% of the mass fraction of iron phosphate and dispersant accounting for 4‰ of the mass fraction of iron phosphate were added with pure water and stirred to form a uniform slurry with a solid content of 48%. The particle size of D50 was adjusted to 0.38μm by sand milling, and then 0.96% of the mass fraction of iron phosphate was added with tin dioxide for stirring and demagnetization to obtain a precursor, which was spray-dried at a temperature of 245°C to control the carbon content of the precursor to 4.65% of the total mass, and then the spray yellow material was crushed by air flow milling to control the crushing D50 to 0.5μm; then, the temperature was increased to 793°C at 5°C / min under a nitrogen protective atmosphere, and the temperature was kept for 12h, and the temperature was cooled to below 120°C by air cooling and water cooling to obtain a lithium iron phosphate positive electrode material with a carbon content of 1.30% of the total mass and a D50 of 0.75μm.

[0067] Example 2 A method for preparing a lithium iron phosphate positive electrode material comprises the following steps: 0.8 mol of methylvinylbis(N-methylacetylamino)silane and 0.3 mol of methyl 3-(dimethylamino)acrylate are added with pure water to prepare a 2.5 mol / L solution, which is then added into a reaction kettle for stirring and heating. When the temperature reaches 65°C, 0.5 mol / L of A solution prepared with 0.08 mol of ammonium persulfate and 10 mol / L of B solution prepared with 4 mol of methacrylic acid, 2 mol of 2-hydroxy-2-methyl-3-butenoic acid and 0.017 mol of mercaptopropionic acid are added dropwise at the same time. The B solution is added dropwise for 50 min, and the A solution is added dropwise for 60 min. During the reaction, the reaction temperature is controlled to be 75°C. After the A solution is added dropwise, the reaction is kept warm for 30 min, and the solution is cooled to room temperature to obtain an aqueous solution of a dispersant with a solid content of 40%; The iron phosphate with an iron-phosphorus ratio of 1:1.03, lithium carbonate accounting for 24.92% of the mass fraction of iron phosphate, monohydrate glucose accounting for 9.8% of the mass fraction of iron phosphate and dispersant accounting for 4‰ of the mass fraction of iron phosphate were added with pure water and stirred to form a uniform slurry with a solid content of 48%. After the particle size of D50 was adjusted to 0.43 μm by sand milling, 0.96% of the mass fraction of iron phosphate was added with tin dioxide and stirred for demagnetization to obtain a precursor, which was spray-dried at a temperature of 245°C to control the carbon content of the precursor to 5.23% of the total mass, and then the spray yellow material was crushed by air flow milling to control the crushing D50 to 0.5 μm; then, the temperature was increased to 793°C at 5°C / min under a nitrogen protective atmosphere, kept warm for 12 hours, cooled to below 120°C by air cooling and water cooling, and then taken out of the furnace to obtain a lithium iron phosphate positive electrode material with a carbon content of 1.29% of the total mass and a D50 of 0.93 μm.

[0068] Example 3 A method for preparing a lithium iron phosphate positive electrode material comprises the following steps: 0.7 mol of methylvinylbis(N-methylacetylamino)silane and 0.4 mol of methyl 3-(dimethylamino)acrylate were added with pure water to prepare a 2.5 mol / L solution, and then added into a reaction kettle for stirring and heating. When the temperature reached 65°C, 0.5 mol / L A solution prepared with 0.08 mol of ammonium persulfate and 10 mol / L B solution prepared with 3 mol of 3-ethoxyacrylic acid, 3 mol of 2-hydroxy-2-methyl-3-butenoic acid and 0.016 mol of mercaptoacetic acid were added dropwise at the same time. The B solution was added dropwise for 50 min, and the A solution was added dropwise for 60 min. During the reaction, the reaction temperature was controlled to be 75°C. After the A solution was added dropwise, the reaction was kept warm for 30 min, and the solution was cooled to room temperature to obtain an aqueous solution of a dispersant with a solid content of 40%; The iron phosphate with an iron-phosphorus ratio of 1:1.03, lithium carbonate accounting for 24.92% of the mass fraction of iron phosphate, monohydrate glucose accounting for 9.8% of the mass fraction of iron phosphate and dispersant accounting for 4‰ of the mass fraction of iron phosphate were added with pure water and stirred to form a uniform slurry with a solid content of 48%. The particle size of D50 was adjusted to 0.40 μm by sand milling, and then 0.96% of the mass fraction of iron phosphate was added with tin dioxide and stirred for demagnetization to obtain a precursor, which was spray-dried at a temperature of 245°C to control the carbon content of the precursor to 5.15% of the total mass. Then, the spray yellow material was crushed by air flow milling to control the crushing D50 to 0.5 μm. Then, the temperature was increased to 793°C at 5°C / min under a nitrogen protective atmosphere, and the temperature was kept for 12h, and the temperature was cooled to below 120°C by air cooling and water cooling to obtain a lithium iron phosphate positive electrode material with a carbon content of 1.30% of the total mass and a D50 of 0.87 μm.

[0069] Example 4 A method for preparing a lithium iron phosphate positive electrode material comprises the following steps: 0.7 mol of methylvinylbis(N-methylacetylamino)silane and 0.4 mol of methyl 3-(dimethylamino)acrylate were added with pure water to prepare a 2.5 mol / L solution, and then added into a reaction kettle for stirring and heating. When the temperature reached 65°C, 0.5 mol / L A solution prepared with 0.08 mol of ammonium persulfate and 10 mol / L B solution prepared with 3 mol of 3-ethoxyacrylic acid, 3 mol of 2-hydroxy-2-methyl-3-butenoic acid and 0.016 mol of mercaptoacetic acid were added dropwise at the same time. The B solution was added dropwise for 50 min, and the A solution was added dropwise for 60 min. During the reaction, the reaction temperature was controlled to be 75°C. After the A solution was added dropwise, the reaction was kept warm for 30 min, and the solution was cooled to room temperature to obtain an aqueous solution of a dispersant with a solid content of 40%; The iron phosphate with an iron-phosphorus ratio of 1:1.03, lithium carbonate accounting for 24.92% of the mass fraction of iron phosphate, monohydrate glucose accounting for 9.8% of the mass fraction of iron phosphate and dispersant accounting for 4‰ of the mass fraction of iron phosphate were added with pure water and stirred to form a uniform slurry with a solid content of 48%. After the particle size of D50 was adjusted to 0.41 μm by sand milling, 0.96% of the mass fraction of iron phosphate and 3:1 of tin dioxide and cerium oxide were added for stirring and demagnetization. The mixture was spray-dried at a temperature of 245°C to control the carbon content of the precursor to 5.20% of the total mass. The spray yellow material was then crushed by air flow milling to control the crushing D50 to 0.5 μm. Then, the mixture was heated to 793°C at a rate of 5°C / min under a nitrogen protective atmosphere, kept warm for 12 hours, cooled to below 120°C by air cooling and water cooling, and then taken out of the furnace to obtain a lithium iron phosphate positive electrode material with a carbon content of 1.30% of the total mass and a D50 of 0.79 μm.

[0070] Example 5 A method for preparing lithium iron phosphate comprises the following steps: 0.7 mol of methylvinylbis(N-methylacetylamino)silane and 0.4 mol of methyl 3-(dimethylamino)acrylate were added with pure water to prepare a 2.5 mol / L solution, and then added into a reaction kettle for stirring and heating. When the temperature reached 65°C, 0.5 mol / L A solution prepared with 0.08 mol of ammonium persulfate and 10 mol / L B solution prepared with 3 mol of 3-ethoxyacrylic acid, 3 mol of 2-hydroxy-2-methyl-3-butenoic acid and 0.016 mol of mercaptoacetic acid were added dropwise at the same time. The B solution was added dropwise for 50 min, and the A solution was added dropwise for 60 min. During the reaction, the reaction temperature was controlled to be 75°C. After the A solution was added dropwise, the reaction was kept warm for 30 min, and the solution was cooled to room temperature to obtain an aqueous solution of a dispersant with a solid content of 40%; The iron phosphate with an iron-phosphorus ratio of 1:1.035, lithium carbonate accounting for 24.92% of the mass fraction of iron phosphate, monohydrate glucose accounting for 9.8% of the mass fraction of iron phosphate and dispersant accounting for 8‰ of the mass fraction of iron phosphate were added with pure water and stirred to form a uniform slurry with a solid content of 48%. The particle size of D50 was adjusted to 0.42 μm by sand milling, and then 0.96% of the mass fraction of iron phosphate and 3:1 of tin dioxide and cerium oxide were added for stirring and demagnetization. The mixture was spray-dried at a temperature of 245°C to control the carbon content of the precursor to 4.88% of the total mass. The spray yellow material was then crushed by air flow milling to control the crushing D50 to 0.5 μm. Then, the mixture was heated to 795°C at a rate of 5°C / min under a nitrogen protective atmosphere, kept warm for 12 hours, cooled to below 120°C by air cooling and water cooling, and then taken out of the furnace to obtain a lithium iron phosphate positive electrode material with a carbon content of 1.28% of the total mass and a D50 of 0.79 μm.

[0071] Example 6 A method for preparing a lithium iron phosphate positive electrode material comprises the following steps: 0.7 mol of methylvinylbis(N-methylacetylamino)silane and 0.4 mol of methyl 3-(dimethylamino)acrylate were added with pure water to prepare a 2.5 mol / L solution, and then added into a reaction kettle for stirring and heating. When the temperature reached 65°C, 0.5 mol / L A solution prepared with 0.08 mol of ammonium persulfate and 10 mol / L B solution prepared with 3 mol of 3-ethoxyacrylic acid, 3 mol of 2-hydroxy-2-methyl-3-butenoic acid and 0.016 mol of mercaptoacetic acid were added dropwise at the same time. The B solution was added dropwise for 50 min, and the A solution was added dropwise for 60 min. During the reaction, the reaction temperature was controlled to be 75°C. After the A solution was added dropwise, the reaction was kept warm for 30 min, and the solution was cooled to room temperature to obtain an aqueous solution of a dispersant with a solid content of 40%; The iron phosphate with an iron-phosphorus ratio of 1:1.035, lithium carbonate accounting for 24.92% of the mass fraction of iron phosphate, monohydrate glucose accounting for 9.8% of the mass fraction of iron phosphate and dispersant accounting for 1.2% of the mass fraction of iron phosphate were added with pure water and stirred to form a uniform slurry with a solid content of 48%. The particle size of D50 was adjusted to 0.39 μm by sand milling, and then 0.96% of the mass fraction of iron phosphate and tin dioxide and cerium oxide in a mass ratio of 2:1 were added for stirring and demagnetization. The mixture was spray-dried at a temperature of 245°C to control the carbon content of the precursor to 4.72% of the total mass. The spray yellow material was then crushed by air flow milling to control the crushing D50 to 0.5 μm. Then, the mixture was heated to 795°C at a rate of 5°C / min under a nitrogen protective atmosphere, kept warm for 12 hours, cooled to below 120°C by air cooling and water cooling, and then taken out of the furnace to obtain a lithium iron phosphate positive electrode material with a carbon content of 1.28% of the total mass and a D50 of 0.91 μm.

[0072] Comparative Example 1 A method for preparing lithium iron phosphate comprises the following steps: Iron phosphate with an iron-phosphorus ratio of 1:1.035, lithium carbonate accounting for 24.92% of the mass fraction of iron phosphate, and monohydrate glucose accounting for 9.8% of the mass fraction of iron phosphate are added with pure water and stirred to form a uniform slurry with a solid content of 48%. After the particle size of D50 is adjusted to 0.38 μm by sand milling, 0.96% of the mass fraction of iron phosphate and 3:1 of tin dioxide and cerium oxide are added for stirring and demagnetization, and spray drying is carried out at a temperature of 245°C to control the carbon content of the precursor to 4.65% of the total mass. The mixture is heated to 795°C at a rate of 5°C / min in a nitrogen protective atmosphere, kept warm for 12 hours, cooled to below 120°C by air cooling and water cooling, and crushed to control D50 at 1.0±0.15 μm. After vibrating and screening to remove iron, lithium iron phosphate positive electrode material powder is obtained, and the carbon content is 1.28% of the total mass.

[0073] Comparative Example 2 A method for preparing lithium iron phosphate, the other contents are the same as those of Example 5, except that the dispersant is replaced by sodium dodecyl sulfate.

[0074] Comparative Example 3 A method for preparing lithium iron phosphate, the other contents are the same as those of Example 5, except that heating to 795°C is replaced by heating to 850°C.

[0075] 2. Test Method The performance of the lithium iron phosphate positive electrode materials obtained in the examples and comparative examples was analyzed: 1) SEM test: Scanning electron microscopy analysis, JSM6390 scanning electron microscope, using NanoMeasurer software to analyze the primary particle size and distribution.

[0076] 2) Particle size distribution: Malvern laser particle size analyzer (MAZ3000), refractive index 1.692, tested dissolved in water, shading degree between 8%-12%.

[0077] 3) Compaction density test: Use a compaction density meter to test, the test pressure is 3T, and the pressing time is 30S.

[0078] 4) BET: Micromeritics TriStar II 3020 surface area analyzer (micromeritics, with nitrogen as adsorbent and helium or hydrogen as carrier gas, the two gases are mixed in a certain ratio to reach a specified relative pressure, and then flow through the solid material. By changing the mixing ratio of nitrogen and carrier gas, the adsorption amount under several relative pressures of nitrogen can be measured, and the specific surface area can be calculated according to the BET formula. 2g sample is degassed and dried at 120℃ for 2h and then tested in a Dewar flask filled with liquid nitrogen.

[0079] 5) Carbon content test: Infrared carbon sulfur analyzer, model HCS-140, Shanghai Dekai Instrument Co., Ltd.

[0080] The lithium iron phosphate cathode materials obtained in the examples and comparative examples were prepared into secondary batteries, and the properties of the secondary batteries were tested respectively: 6) Lithium iron phosphate gram capacity test: Blue electricity test, using the prepared material as the positive electrode material, acetylene black as the conductive agent, polytetrafluoroethylene as the binder, and making the electrode sheet according to the mass ratio of 90:5:5, with metal lithium as the negative electrode, assembled into a CR2032 button battery. Test 1C charge and discharge at 2~3.75V, 25±0.5℃, and charge and discharge at 1P constant power at 2.5~3.75V, 25±0.5℃.

[0081] III. Analysis of test results of various embodiments and comparative examples The basic performance test results of the finished lithium iron phosphate cathode materials after sintering of the embodiments and comparative examples are shown in Tables 1 and 2; wherein Table 1 shows the basic physical and chemical performance data of the lithium iron phosphate cathode materials, and the chemical formula and carbon content are designed according to the formula.

[0082] Table 1 Physical and chemical properties test results

[0083] It can be seen from Table 1 that the compaction density of the lithium iron phosphate positive electrode material prepared in the present application is higher than the compaction density of the lithium iron phosphate positive electrode material prepared in the comparative example.

[0084] Further, Figure 1 This is a SEM image of the lithium iron phosphate positive electrode material of Example 5; Figure 2 This is a particle size distribution detection diagram of the lithium iron phosphate positive electrode material of Example 5; Figure 3 This is the SEM image of the lithium iron phosphate positive electrode material of Comparative Example 1. Figure 4 This is a particle size distribution detection diagram of the lithium iron phosphate positive electrode material of Comparative Example 1; Figures 1 to 4 It can be seen from the content shown that the lithium iron phosphate particles in Example 5 of the present application have better dispersibility, no obvious large particle agglomerates, and correspond to the test results of the laser particle size analyzer, that is, the volume proportion of small particles is higher, the particle distribution range is wider, the grading effect is better, and the compaction density is higher. In Comparative Example 1, there are obviously more large agglomerates. The appearance of large particle agglomerates is mainly due to the thin carbon layer on the surface of large particles. During the sintering process, particles that are close to each other will form sintering necks and slowly fuse into larger agglomerates, resulting in a larger porosity of the agglomerates, and the compaction density of the obtained lithium iron phosphate positive electrode material is low.

[0085] Further, Figure 5The Raman spectra test results of the lithium iron phosphate positive electrode materials prepared in Example 5 and Comparative Example 1 are as follows; Figure 5 As shown, the G peak of the lithium iron phosphate positive electrode material prepared in Example 5 is significantly higher than the D peak, indicating that sintering after adding a dispersant can significantly improve the graphitization degree of carbon, thereby making the prepared lithium iron phosphate positive electrode material have better conductivity.

[0086] Further, Figure 6 The particle size distribution curves of the crushed lithium iron phosphate positive electrode materials of Example 3, Example 5 and Comparative Example 1 show that the proportion of small particles of the prepared lithium iron phosphate positive electrode material gradually increases after the addition of the dispersant, and the size of the small particles is smaller, indicating that after the dispersant is added during the preparation of the lithium iron phosphate positive electrode material, the small particles of the prepared lithium iron phosphate positive electrode material have better dispersibility.

[0087] Table 2 Capacity test

[0088] Table 2 compares the charge and discharge performance data of lithium iron phosphate of different schemes, among which the difference in 0.1C charge and discharge performance is relatively small, but the 1C first discharge specific capacity of the embodiment is significantly better than the 1C first discharge specific capacity of the comparative example. At the same time, the 1C first discharge efficiency of the embodiment is also significantly better than the 1C first discharge efficiency of the comparative example. Therefore, the compaction density and electrochemical performance of the lithium iron phosphate positive electrode material prepared in the present application are improved.

[0089] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing a dispersant, characterized in that: The method comprises the following steps: taking a first monomer, a second monomer, a chain transfer agent and an initiator as raw materials, and carrying out a polymerization reaction at 45-75° C. to obtain the dispersant; wherein the first monomer comprises one or more of diethylmethylvinylsilane, methylvinylbis(N-methylacetylamino)silane and 3-(dimethylamino)methylacrylate, and the second monomer comprises one or more of methacrylic acid, 3-ethoxyacrylic acid and 2-hydroxy-2-methyl-3-butenoic acid.

2. The method for preparing a dispersant according to claim 1, characterized in that: The chain transfer agent comprises at least one of mercaptoacetic acid and mercaptopropionic acid; and / or, The initiator includes at least one of azobisisobutyronitrile and ammonium persulfate.

3. The method for preparing a dispersant according to claim 1, characterized in that: The molar ratio of the first monomer, the second monomer, the chain transfer agent, and the initiator is 1:(5-8):(0.015-0.02):(0.05-0.10).

4. A dispersant, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 3.

5. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: Adding anhydrous ferric phosphate, a lithium source, a carbon source, and a dispersant into a solvent and mixing to obtain a slurry; The slurry is dispersed, and then a dopant is added to the slurry to obtain a precursor slurry; The precursor slurry is spray-dried, airflow-pulverized, and sintered in sequence to obtain the lithium iron phosphate; Wherein, the dispersant is the dispersant according to claim 4.

6. The method for preparing the lithium iron phosphate positive electrode material according to claim 5, characterized in that: The solid content of the slurry is 45%-50%, and the density of the slurry is ≥1.2g / cm 3 and / or, The D50 of the slurry after dispersion treatment is 0.36-0.45 μm, and Dmax is ≤1.15 μm; and / or, The process parameters of the air flow milling include: the pressure of the air flow milling is 0.48-0.52MPa, the frequency of the classifying wheel is 20-60Hz, and the feeding frequency is 6-18Hz; and / or, The D50 of the particles after the airflow pulverization is 0.6-1.2 μm, and Dmax is ≤15 μm.

7. The method for preparing a lithium iron phosphate positive electrode material according to claim 5, characterized in that: The mass ratio of the anhydrous ferric phosphate to the lithium source, the carbon source and the dispersant is 100:(22-26):(8-12):(0.4-1.2); and / or The mass ratio of the dispersant to the dopant is (0.41-0.85):1; and / or The carbon source includes at least one of glucose and sucrose; and / or, The dopant includes at least one of tin dioxide, titanium dioxide and cerium oxide; The lithium source includes at least one of lithium carbonate, lithium chloride, lithium nitrate and lithium hydroxide.

8. The method for preparing a lithium iron phosphate positive electrode material according to claim 5, characterized in that: The sintering temperature is 790-800° C., and the sintering atmosphere is an inert atmosphere.

9. A lithium iron phosphate positive electrode material, characterized in that: It is prepared by the preparation method according to any one of claims 5 to 8, wherein the 1C discharge specific capacity of the lithium iron phosphate positive electrode material is 146-147 mAh / g; and the compaction density of the lithium iron phosphate positive electrode material is 2.62-2.68 g / mL.

10. A secondary battery, characterized in that: It includes the lithium iron phosphate positive electrode material as claimed in claim 9.

Citation Information

Cited By

  • Ilmenite flotation dispersing agent, preparation method thereof and ilmenite flotation method

    CN120094748A